A Study on The Influence of Cosmetology University Students on The Intention to Entrepreneurship and Revitalization of Entrepreneurship - Yoon, Mi-yun (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The Government and universities are conducting undertaking various programs related to start-ups. Nevertheless, still point out that college graduates' performance in starting their own businesses is insufficient. Methods: To investigate, using the structural equation modeling, what influences on the intention of undergraduate students in beauty sector to start their own business. We conducted the self-administered questionnaire during the period between October 1, 2019 and December 31, 2019 for undergraduate students who have had experiences with entrepreneurship education or lecture for business startup for the past 5 years and also have are willing to start their own business. Findings: The entrepreneurship capability shall have positive (+) influence over the entrepreneurship opportunity recognition (adopted). The entrepreneurship education shall have positive (+) influence over the entrepreneurial self-efficacy (adopted). The entrepreneurship shall have positive (+) influence over the entrepreneurial self-efficacy (adopted). The entrepreneurship capacity shall have positive (+) influence over the entrepreneurial self-efficacy (adopted). The entrepreneurship support shall have positive (+) influence over the entrepreneurial self-efficacy (adopted). The entrepreneurship opportunity recognition shall have positive (+) influence over the entrepreneurial self-efficacy (adopted). The entrepreneurship opportunity recognition shall have positive (+) influence over the entrepreneurship intentions (adopted). The entrepreneurial self-efficacy shall have positive (+) influence over the entrepreneurship intentions (adopted). In conclusion, it was found when the factors of the entrepreneurship education, the entrepreneurship, the entrepreneurship capacity, and the entrepreneurship opportunity recognition were strong, so did the entrepreneurial self-efficacy and eventually the entrepreneurship intention was further buoyed. Therefore, it is necessary to establish the entrepreneurship strategy in consideration of this result. Applications: College students' start-up education should be conducted from the perspective of educating students to become start-ups, and classes should be designed so that they can have related experiences rather than theories.